Urban commons: social resilience experiences to increase the quality of urban system - Esopi, Giulia (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The present paper defines a specific typology of urban commons and aims to show how these are social resilience based phenomena that can increase the quality of urban system. The contemporary urban studies debate intends the city as a complex system that interacts with other cities creating a complex global network. At the same time, the city is subject to continuous and rapid changes that generate instability conditions and make it fragile. The institutions, responsible for territory sustainable development, struggle to deal with these phenomena generating situations of inefficiency and poor functioning of city system and its parts. In example, the inability of institutions to manage the territory is represented in static and rigid space arrangements of a fluid system. These situations cause the misuse/under-use of spaces and services by society and the dissatisfaction of city users needs. In an attempt to fill the gap left by public actors, community initiatives are emerging from below aimed to shape urban space creating new opportunities for community use. These are forms of collaboration and cooperation among different individuals that take responsibility for urban resources by satisfying both collective and individual needs. They are social resilience experiences, or rather reactions-actions by individuals that represent alternatives to traditional planning. The social component abilities (reactive, adaptive and proactive) increase the quality of urban system in terms of enhancement, sustainability and attractiveness. From these interaction among physical elements and individuals, new forms of wealth are generated as urban commons.